1992
DOI: 10.1007/bf00296560
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of diastematomyelia: can a surgical model in the chick embryo give some clues about the human malformation?

Abstract: To reproduce diastematomyelia, a sagittal incision was carried out at the level of the rhomboidal sinus of 36- to 40-h-old chick embryos. A small piece of membrane shell, a small agar screen, or a piece of quail isochronous isotopic notochord was inserted into the gap. The embryos were killed and fixed after 9 days' incubation. Diastematomyelia was obtained in several embryos treated with interposition of a membrane screen or a piece of quail notochord. Microscopic examination revealed two hemicords, each cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, the notochords in these embryos were not split at the same level as seen in SCM. Similar malformations have also been observed in avian embryos [6]. In our present study, an experimental animal model of SCM was produced by the surgical induction of a fistula that mimicked a neurenteric canal, and we examined the relationship between an accessory neurenteric canal and SCM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the notochords in these embryos were not split at the same level as seen in SCM. Similar malformations have also been observed in avian embryos [6]. In our present study, an experimental animal model of SCM was produced by the surgical induction of a fistula that mimicked a neurenteric canal, and we examined the relationship between an accessory neurenteric canal and SCM.…”
Section: Discussionmentioning
confidence: 97%
“…Klessinger et al [5]and Rilliet et al [6]reported an experimental animal model for this condition in avian embryos. In this present study, we experimentally produced SCM in Cynopus pyrrhogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of a suitable animal model, none of the hypotheses have been verified experimentally, despite experimental models that show split neural tubes in embryos [6, 7, 8, 13]. This is the first report of an experimental animal model of ‘true split cord malformation’, in which double spinal cords were developed in the spinal canal.…”
Section: Introductionmentioning
confidence: 97%
“…3 Recent surgical models involving chick embryos have lent credence to these theories, demonstrating that a resorbable agar screen does not induce an SCM, whereas an implanted membrane shell or notochord does induce the formation of a split cord. 19 These results provide evidence in opposition to the aberrant primary neurulation hypothesis of SCM. Instead, noninvolution of a firm midline structure prevents fusion and allows infiltration of mesodermal cells from the notochord.…”
Section: Discussionmentioning
confidence: 82%